Reconstruction of the Islamic Education Paradigm; Fazlur Rahman’s Thought Inovation - Herwati; Abu Bakar, M. Yunus; Mas'ud, Ali (Mu'allim, 2026)
Reconstructing the paradigm of Islamic education has become an urgent necessity in response to the dynamic development of knowledge and the challenges of modernization. This study examines Fazlur Rahman’s alternative ideas as an effort to renew Islamic education through a library research approach. Fazlur Rahman proposes three innovative main approaches: the Islamization of modern secular education as an effort to integrate Islamic values into the contemporary education system; the simplification of the traditional syllabus to align learning materials with current needs; and the integration of classical branches of knowledge with modern sciences to create a holistic and relevant curriculum. This study emphasizes that these three approaches not only have the potential to overcome the stagnation of Islamic education but also open space for educational transformation that can compete globally without losing its Islamic identity. The findings are expected to serve as a conceptual foundation for educators and policymakers in formulating progressive and adaptive strategies for renewing Islamic education.